Constance Classen, David Howes & Anthony Synnott: Aroma: The Cullural History of Smell - Katz, Joel Leonard (Tidsskriftet Antropologi, 2019)
Aroma: The Cullural History of Smell Anmeldes af Joel Leonard Katz